Investigating Data Cleaning Methods to Improve Performance of Brain–Computer Interfaces Based on Stereo-Electroencephalography - Liu, Shengjie; Li, Guangye; Jiang, Shize; Wu, Xiaolong; Hu, Jie; Zhang, Dingguo; Chen, Liang (Frontiers in Neuroscience, 2021)
Stereo-electroencephalography (SEEG) utilizes localized and penetrating depth electrodes to directly measure electrophysiological brain activity. The implanted electrodes generally provide a sparse sampling of multiple brain regions including both cortical and subcortical structures, making the SEEG neural recordings a potential source for brain computer interface (BCI) purpose in recent years. For SEEG signals, data cleaning is an essential pre-processing step in removing excessive noises for further analysis. However, little is known about what kinds of effect that different data cleaning methods may exert on BCI decoding performance, and moreover, what are the reasons causing the differentiated effects. To address these questions, we adopted five different data cleaning methods, including common average reference (CAR), gray-white matter reference (GWR), electrode shaft reference (ESR), bipolar reference and Laplacian reference, to process the SEEG data and evaluated the effect of these methods on improving BCI decoding performance. Additionally, we also comparatively investigated the changes of SEEG signals induced by these different methods from multiple-domain (e.g., spatial, spectral, and temporal domain). The results showed that data cleaning methods could improve the accuracy of gesture decoding, where Laplacian reference produced the best performance. Further analysis revealed that the superiority of the data cleaning method with excellent performance may be attributed to the increased distinguishability in low-frequency band. The findings of this work highlighted the importance of applying proper data clean methods for SEEG signals and proposed the application of Laplacian reference for SEEG-based BCI.